Biochemistry and Renal Function: Use of Inquiry-Based Teaching Sequences for Retrieval of Specific Concepts - Magalhães, Prislaine Pupolin [UNESP] (2020)
Current teaching proposals involve teaching strategies that seek to assist and encourage the construction of knowledge by the students, turning them into active participants during the learning process and these have been the subject of several researches. This article reports a didactic sequence carried out with students of applied training for the first year Medical Sciences USP – Bauru, and proposes, as part of its pedagogical design, Problem Based Learning (PBL) as the main teaching strategy. In this didactic sequence we used experimental investigative activities. A didactic sequence that includes investigative activities can be characterized as a gradual evolutionary process, with the objective of intertwining the scientific perspective and the students’ conceptions, through well-planned teaching and learning activities contextualized and empirically adapted to the student’s reasoning. The objective of this work is to share an assertive experience of the application of a contextualized research didactic sequence that involved concepts ranging from the simplest chemical properties of biomolecules and ions to the association and discussion of a hypothetical clinical case involving proteinuria. Its pathophysiology consists of the excretion of protein in the urine, mainly albumin, and occurs when there is some damage to the kidneys. Therefore, the dosage of the protein fraction in urine (albuminuria) is mainly used for the early detection of chronic or acute kidney disease and can also be an instrument for the diagnosis of cardiovascular diseases. Therefore, one should be aware of the possible interferences and the various causes of errors inherent to this examination. In this way, through a didactic resource involving contextualized research experimental activities, having proteinuria as the key problem, we were able to re-approximate specific concepts and to value procedural and attitudinal knowledge, which is important for students in this training phase. In this proposal, the students were protagonists of the learning process, where they were able to raise and test their hypotheses, interconnecting knowledge, acquiring specific skills and competences, allowing reflection on the importance of fundamentals and applications of the basic sciences. The purpose of the investigative and contextualized didactic sequences is to form autonomous subjects, who know how to make decisions and work in teams and have a sound and critical understanding of how scientific knowledge evolves and is related.